Export Supply of Electricity from Laos to Thailand: An Econometric Analysis - Lamphayphan, Thongphet; Toyoda, Toshihisa; Czerkawski, Chris; Kyophilavong, Phouphet (International Journal of Energy Economics and Policy, 2015)
Thailand, as the largest electricity market for Laos, has imported significant amounts of electricity from Laos since the operation of first hydropower plant in Laos. However, currently there have been a number of new power particularly nuclear power plants in Thailand being studied implying the possibility of reduction in Thailand’s electricity import from Laos. Since Thailand is the largest market of Laos’ electricity, the change in demand for electricity from Thailand has substantial impact on the Lao economy. The first simulation conducted in this paper shows that Thailand reduces the import of electricity from Laos shows that it statistically has a large impact on Laos’ electricity export sector, due to the reduction of income from electricity export. However, the feasibility of nuclear power projects in Thailand became unclear since the incident of damages of nuclear power plants in Japan on 11 March 2011. Therefore, there may be a possibility that Thailand may abolish the nuclear power projects. Consequently, Thailand may increase the import of electricity from Laos. The second case of simulation shows that the increase of Thailand’s electricity import from Laos has positive effect on Lao economy through the significant increase in income from electricity export. The increase in Thailand’s electricity import from Laos, not only has positive effect on Thai economy in terms of increasing consumption of electricity stimulating economic activities in Thailand, but it also has positive effect on Lao economy in terms of increasing income from electricity export. Keywords: Electricity Export; Laos; Simultaneous effects; Thailand JEL Classifications: C5; Q43